Effects of Moral Values on Individuals and Society and Its Relation to Economic Development: An Analytical Study - Rahman, Mohammad Maseehur (International Journal of Shari'ah and Corporate Governance Research, 2018)
Moral and ethical values guide a person to differentiate what is good and wrong, and provides an acceptable code of behaviors that all members of a particular society are supposed to follow so as to live in peace and harmony. On the other hand, there are a strong relationship between moral values and economic development of society as well as country. The article aims to describe effects of moral values on individuals and society. It also aims to discover the relationship between development of society and moral values through applying analytical method. The study cleared that deterioration of moral values, ethical values; common manners, respect, civility and proper etiquette have impacted negatively on the individuals and modern society.